An object-identity probability cueing paradigm during grasping observation: the facilitating effect is present only when the observed kinematics is suitable for the cued object - Craighero, Laila; Mele, Sonia; Zorzi, Valentina (Frontiers in Psychology, 2015)
Electrophysiological and psychophysical data indicate that grasping observation automatically orients attention towards the incoming interactions between the actor’s hand and the object. The aim of the present study was to clarify if this effect facilitates the detection of a graspable object with the observed action as compared to an ungraspable one. We submitted participants to an object-identity probability cueing experiment in which the two possible targets were of the same dimensions but one of them presented sharp tips at one extreme while the other presented flat faces. At the beginning of each trial the most probable target was briefly shown. After a variable interval, at the same position, the same (75%) or a different target (25%) was presented. Participants had to press a key in response to target appearance. Superimposed to the video showing cue and target, an agent performing the reaching and grasping of the target was presented. The kinematics of the action was or was not suitable for grasping the cued target, according to the absence or presence of the sharp tips. Results showed that response was modulated by the probability of target identity but only when the observed kinematics was suitable to grasp the attended target. A further experiment clarified that response modulation was never present when the superimposed video always showed the agent at a rest position. These findings are discussed at the light of neurophysiological and psychophysical literature, considering the relationship between the motor system and the perception of objects and of others’ actions. We conclude that the prediction of the mechanical events that arise from the interactions between the hand and the attended object is at the basis of the capability to select a graspable object in space.